Exploration of gender dynamics in the production and marketing of forage technologies in Kenya - Njiru, Nelly; Galiè, Alessandra; Wanyoike, Francis N.; Tawanda, M.; Boonabaana, B.; Bisikwa, J.; Njuguna-Mungai, Esther; Jones, Christopher S.; Baltenweck, Isabelle (Frontiers Media, 2023)
Inadequate and poor-quality feed resources are a key constraining factor in livestock production that compromises the livelihoods of many women and men dependent on livestock, who can be found in most low- and middle-income countries (LMICs). Several forage varieties have been developed, which are targeted to smallholder farmers in developing countries, yet the level of adoption remains low, particularly among women farmers. Adoption of varieties could enhance livelihoods by increasing livestock productivity and also by providing an income from the sale of surplus forage. However, evidence on gendered barriers to and incentives for the adoption of forage varieties is scarce. This study explores the gender dynamics influencing the uptake and commercialization of a forage variety, Brachiaria (syn. Urochloa), among women and men farmers in four subcounties in Kenya. Through a mixed-methods approach, 260 individuals (59 women and 201 men) belonging to a household where at least one individual is a member of a dairy cooperative were interviewed. Complementary data from qualitative interviews engaging 16 single-sex focus group discussions (FGDs) and 8 key informant interviews (KIIs) were collected. Results reveal that Brachiaria is accessible to both women and men. Dairy cooperatives are important means for women and men to access extension services, useful information, and planting materials, but only a few women are cooperative members. Men face constraints owing to small land areas, rather than the ownership and access problems that constrain women. These challenges privilege men as de facto owners of resources while subordinating women and disenfranchising them in terms of adopting this technology. Complex yet important pathways for women’s and men’s empowerment exist through the sale of planting materials, hay bales, and an increased volume of milk obtained when cows are fed with Brachiaria. We conclude that cooperative membership for men should be supported, while at the same time gender norms that reduce women’s engagement with cooperatives, and their access to and control over land, should be challenged.